Millennials and Digital Wallets: Addressing Consumer Behavior in the Technology Era - Widodo, Andeka; Amelia, Rizki Lala (Faculty of Economics and Business, Universitas Klabat, 2026)
In Indonesia, the use of digital wallets (e-wallets) such as GoPay, OVO, DANA, and ShopeePay is increasing, especially among the millennial generation who prioritize ease and speed of transactions. This study aims to analyze the factors that influence student consumer behavior in using digital wallets. The method used is qualitative with a phenomenological approach. Based on a Populix survey of 1,000 respondents, the most widely used digital wallet applications are Dana (88%), Gopay (83%), ShopeePay (79%), OVO (76%), and LinkAja! (30%). The results of the study show that ease of access, cashback, and promotions play a significant role in encouraging the use of digital wallets. However, low financial literacy leads to a tendency towards uncontrolled consumer behavior. Therefore, education about financial literacy is an important aspect in using digital wallets wisely.